Effect of the degree of esterification and blockiness on the complex coacervation of pea protein isolate and commercial pectic polysaccharides. (30th October 2018) - Warnakulasuriya, Sumudu; Pillai, Prasanth K.S.; Stone, Andrea K.; Nickerson, Michael T.
Highlights: Pea protein forms coacervates with pectin at specific mixing ratios and pHs. Coacervation is highly dependent on the physicochemical properties of pectin. Higher degrees of esterification and blockiness of pectin increase complex formation. Pectin can improve the solubility of pea protein at pH 4.5. Abstract: The complex coacervation of pea protein isolate (PPI) with commercial pectic polysaccharides [high methoxy citrus pectin (P90, 90 representing DE), apple pectin (P78) sugar beet pectin (P62), low methoxy citrus pectin (P29)] of different degrees of esterification (DE) [and galacturonic acid content (GalA)] and blockiness (DB), was investigated. The maximum amount of coacervates formed at a biopolymer weight mixing ratio of 4:1 for all PPI-pectin mixtures, with the exception of PPI-P29 where maximum coacervation occurred at the 10:1 mixing ratio. The pH at which maximum interactions occurred was pH 3.4–3.5 (PPI: P90/P78) and 3.7–3.8 (PPI: P62/P29). PPI complexed with pectins with high levels of DE (low levels of GalA) and DB displayed greater interactions at optimal mixing conditions compared to pectin having lower levels of esterification and blockiness. The addition of P78 to PPI greatly increased protein solubility at pH 4.5.